Tractable Term Structure Models - Feunou, Bruno; Fontaine, Jean-Sébastien; Le, Anh; Lundblad, Christian (Management Science, 2022)
We introduce a new framework that facilitates term structure modeling with both positive interest rates and flexible time series dynamics but that is also tractable, meaning amenable to quick and robust estimation. Using both simulations and U.S. historical data, we compare our approach with benchmark Gaussian and stochastic volatility models as well as a shadow rate model that enforces positive interest rates. Our approach, which remains arbitrarily close to arbitrage free, offers a more accurate characterization of bond Sharpe ratios because of a better fit of the volatility dynamics and a more efficient estimation of the return dynamics. Further, the shadow rate and stochastic volatility models exhibit important restrictions that are largely absent in our approach. This paper was accepted by Agostino Capponi, finance. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2021.4214 .